2014
DOI: 10.1111/nep.12271
|View full text |Cite
|
Sign up to set email alerts
|

Berberine ameliorates renal interstitial fibrosis induced by unilateral ureteral obstruction in rats

Abstract: Berberine treatment ameliorates RIF in a UUO rat model by inhibition of oxidative stress, inflammatory responses, and TGF-β1/pSmad3 signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 28 publications
(52 reference statements)
2
13
0
Order By: Relevance
“…Poricoic acid G and poricoic acid H suppressed TGF-β/Smad pathway by selectively inhibiting the phosphorylation of Smad3 via blocking the interactions of SARA with TGFβRI and Smad3 [178]. Similarly, renal fibrosis in a variety of animal models were attenuated or suppressed through TGF-β/Smads and NF-κB-mediated pathways by administration of compounds isolated from various natural products, such as GQ5 [179], arctigenin [98], curcumin [180,181], resveratrol [182], berberine [183,184], sinomenine [185], rutin [186], oxymatrine [149,187], bergenin [188], oleanolic acid [189], tanshinone IIA [190], leonurine [191]; (+/−)-sinensilactam A [192], epigallocatechin-3-gallate [193] and astragaloside IV [194,195].…”
Section: Specific Inhibition Of Smads Signaling By Natural Productsmentioning
confidence: 99%
“…Poricoic acid G and poricoic acid H suppressed TGF-β/Smad pathway by selectively inhibiting the phosphorylation of Smad3 via blocking the interactions of SARA with TGFβRI and Smad3 [178]. Similarly, renal fibrosis in a variety of animal models were attenuated or suppressed through TGF-β/Smads and NF-κB-mediated pathways by administration of compounds isolated from various natural products, such as GQ5 [179], arctigenin [98], curcumin [180,181], resveratrol [182], berberine [183,184], sinomenine [185], rutin [186], oxymatrine [149,187], bergenin [188], oleanolic acid [189], tanshinone IIA [190], leonurine [191]; (+/−)-sinensilactam A [192], epigallocatechin-3-gallate [193] and astragaloside IV [194,195].…”
Section: Specific Inhibition Of Smads Signaling By Natural Productsmentioning
confidence: 99%
“…It is an antimicrobial drug routinely prescribed for the treatment of diarrhea in various Asian countries ( 11 ). In addition to this well-known and widely recognized effect, it has been demonstrated that BBR also regulates the activity of transcription factors essential for the inflammatory response ( 12 ). BBR has been shown to provide intestinal and cerebral protection against I/R-induced injury ( 13 , 14 ); however, the effects of BBR against myocardial I/R injury are yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…15 Similarly, another rodent model also described that berberine treatment improves renal interstitial fibrosis of obstructed kidney. 16 In addition, it has also been documented that berberine ameliorates hypertension-induced renal damage in spontaneous hypertensive rats. 17 However, the effect of berberine in association with GM-induced nephrotoxicity has been not explored.…”
Section: Introductionmentioning
confidence: 99%